Integrasi Ekonomi Sirkular dalam Industri Kimia untuk Pembangunan Berkelanjutan : Tinjauan Literatur - Lintang Rizkyta Ananda; Rendy Mukti; Rizki Triguna; Robby Mubarok (Politeknik Kampar, 2024)
This study aims to explore the integration of circular economy in the chemical industry over the past decade, specifically from 2015 to 2025, using the systematic literature review (slr) method. data were analyzed using the prisma flow diagram, which maps inclusion activities and search results. journal articles were identified from the sciencedirect database. out of a total of 34,885 articles spanning 10 disciplines, the research focus was narrowed down to chemical engineering. following a selection process from 3,819 articles, 1,027 articles were identified as meeting the criteria for further analysis. articles that fulfilled the inclusion criteria were then selected for in-depth review. the study results indicate that research on the circular economy in the chemical industry has experienced rapid growth and has become a significant trend, driving the industry's attention toward environmental impact. data analysis shows that 2024 recorded the highest number of article publications, with a total of 438 articles, while the article with the highest number of citations was published in 2022, with 333 citations.